The Oracle of Rebekah: An Ambiguous Etiology - Aikhler, Raʿanan (Biblica, 2019)
This paper seeks to identify a new type of deliberate literary ambiguity in the Hebrew Bible: the ambiguous etiology, which is an etiology designed to account for a complex or changing reality by embodying its contradictory aspects in the same statement. The example given to illustrate this type is the Yahwistic Oracle of Rebekah (Gen 25,23), which is clearly an etiology for the relations between Israel and Edom. The final, key clause of this oracle seems to predict which nation will subjugate the other. It is argued that the prediction is complicated by the clause's containing four independent forms of ambiguity, which are drawn out in the continuation of the Yahwistic narrative. The oracle thus accounts for the continually oscillating power relationship between the two nations.